Governing global-city Singapore : legacies and futures after Lee Kuan Yew - Tan, Kenneth Paul (London ; New York, : Routledge, Taylor & Francis Group, 2017)
'Provides a detailed analysis of how governance in Singapore has evolved since independence to become what it is today, and what its prospects might be in a post-Lee Kuan Yew future. Firstly, it discusses the question of political leadership, electoral dominance and legislative monopoly in Singapore's one-party dominant system and the system's durability. Secondly, it tracks developments in Singapore's public administration, critically analysing the formation and transformation of meritocracy and pragmatism, two key components of the state ideology. Thirdly, it discusses developments within civil society, focusing in particular on issues related to patriarchy and feminism, hetero-normativity and gay activism, immigration and migrant worker exploitation, and the contest over history and national narratives in academia, the media and the arts. Fourthly, it discusses the PAP government's efforts to connect with the public, including its national public engagement exercises that can be interpreted as a subtler approach to social and political control. In increasingly complex conditions, the state struggles to maintain its hegemony while securing a pre-eminent position in the global economic order. Tan demonstrates how trends in these four areas converge in ways that signal plausible futures for a post-LKY Singapore'--
Singapore's dominant party system -- Harnessing talent for a macho-meritocratic elite -- Pragmatism and the neoliberal state -- The patriarchal state's feminization of civil society -- Gay activism, religious conservatism, and the policing of neoliberal crises -- Moral panic and the migrant worker folk devil -- Inventing and re-inventing the public -- The Singapore story : censorship and nostalgia in the creative city -- Imagining futures after Lee Kuan Yew.
Includes bibliographical references and index.
Keywords: Singapore -- Politics and government -- 21st century